Spatial Extent of Fluorescence Quenching in Mixed Semiconductor–Metal Nanoparticle Gel Networks (Adv. Funct. Mater. 41/2021). (7th October 2021) - Rosebrock, Marina; Zámbó, Dániel; Rusch, Pascal; Pluta, Denis; Steinbach, Frank; Bessel, Patrick; Schlosser, Anja; Feldhoff, Armin; Hindricks, Karen D. J.; Behrens, Peter; Dorfs, Dirk; Bigall, Nadja C.
Abstract : Semiconductor Gel Networks In article number 2101628, Nadja C. Bigall and co‐workers demonstrate that a single gold nanoparticle is able to quench the fluorescence of up to 9 semiconductor nanorods in mixed, co‐gelated gel networks. Upon varying the particle number ratio of CdSe/CdS and Au nanocrystals, the spatial extent of quenching, thus, the travel distance of photoexcited electrons is changed within the interconnected semiconductor backbone.